Application of Ice Breaking in Increasing The Concentration of Female Futsal Athletes - Oktrina, Trias Kartika; Perwira Bakti, Ananda; Pudjijuniarto, Pudjijuniarto; Fithroni, Hijrin (Universitas PGRI Palembang, 2024)
Futsal sports revealed that the ice breaking technique was effective in increasing the concentration of female futsal athletes at the El-Wafa Airwomen club. This research aims to determine whether ice breaking techniques can increase the concentration of female futsal athletes from the Airwomen El-Wafa club. The research method used was descriptive quantitative with a one group pretest-posttest experimental design, involving 20 athletes as samples. The ice breaking that is implemented includes gathering games, counting, shouting